2019
DOI: 10.3389/fpls.2019.01105
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domains SnRK2 Box and ABA Box Have a Role in Sugarcane SnRK2s Auto-Activation and Activity

Abstract: Resistance to drought stress is fundamental to plant survival and development. Abscisic acid (ABA) is one of the major hormones involved in different types of abiotic and biotic stress responses. ABA intracellular signaling has been extensively explored in Arabidopsis thaliana and occurs via a phosphorylation cascade mediated by three related protein kinases, denominated SnRK2s (SNF1-related protein kinases). However, the role of ABA signaling and the biochemistry of SnRK2 in crop plants remains underexplored.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…On the other hand, in in vivo conditions, the process of closing the stomata in these mutants was disturbed, which would indicate that the activation of further components of the ABA signaling pathway depends on the phosphorylation of amino acid positions within this SnRK2 domain [54,100]. This was confirmed by the data obtained by Righetto et al [101], using recombinant stress-activated SnRK2 regulatory domains (ABA-activated protein kinases; SAPK) isolated from sugar cane. It was shown that, in ScSAPK8, deletion of the ABA cassette led to a reduction in the number of autophosphorylated sites in the protein.…”
Section: Model Of the Pp2c-snrk2 Interactionsupporting
confidence: 54%
“…On the other hand, in in vivo conditions, the process of closing the stomata in these mutants was disturbed, which would indicate that the activation of further components of the ABA signaling pathway depends on the phosphorylation of amino acid positions within this SnRK2 domain [54,100]. This was confirmed by the data obtained by Righetto et al [101], using recombinant stress-activated SnRK2 regulatory domains (ABA-activated protein kinases; SAPK) isolated from sugar cane. It was shown that, in ScSAPK8, deletion of the ABA cassette led to a reduction in the number of autophosphorylated sites in the protein.…”
Section: Model Of the Pp2c-snrk2 Interactionsupporting
confidence: 54%